Carbon and nitrogen storage, and inorganic nitrogen forms in a soil under different management systems - d'Andréa, Alexandre Fonseca; Silva, Marx Leandro Naves; Curi, Nilton; Guilherme, Luiz Roberto Guimarães (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to verify alterations on the amounts and storage of organic carbon and total nitrogen of the soil, and on the nitric and ammonium forms, in management systems implemented in an area under native cerrado. Samples were collected at Morrinhos, Goiás, Brazil, in a clayey, typic, dystrophic Red Latosol (Oxisol), from five depths, in the systems: native cerrado, Brachiaria sp. pasture, irrigated no-till with corn-beans crop rotation, irrigated no-till with corn-beans and rice-tomato for industry crop rotation, long-term conventional till and recent conventional till following pasture. There were no significant differences on the level, and on carbon and total nitrogen storage of the soil. However, the long-term conventional till presented negative variations on carbon storage in relation to the native cerrado system up to 20 cm depth, unlike the systems with less soil movement. The ammonium predominated in the native cerrado and pasture systems through the soil profile, whereas the nitrate amounts were higher in the superficial layer of the soil in the systems with annual crops. The pasture and no-till, on condition of diverse crop rotation, are prominent systems in terms of increasing the organic carbon storage of the soil.